Why do not all living kidney donor candidates proceed to donation?. Issue 3 (21st March 2019) - Cash, Ellie; Graver, Alison; Kuo, Stephanie; Kirkland, Geoffrey; Hughes, Peter; Robertson, Amanda; Jose, Matthew D.
Abstract: There are national and international guidelines for donor workup and acceptance criteria of potential living kidney donor candidates (LKDC), but there is significant variation in clinical practice. We examined our local practice in assessing potential LKDC against current guidelines; nearly all of our accepted donors met these guidelines. LKDC who did not proceed to donation had an identified health issue (60%), the presence of risk factors for long‐term end‐stage kidney disease (17%), social (13%) or immunological reasons (7%).